The analysis of trafficking in persons from a human rights perspective (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
Human trafficking is a crime that seriously infringe the victims’ human rights who become invisible. It is defined by the United Nations (2000) like “a sequence of criminal activities whose purpose includes different forms of exploitation”. This crime is considered a contemporary form of slavery that has evolved with globalization. It has different purposes that include sexual exploitation and labour exploitation, but also slavery and similar practices, the extraction of organs, etc. Sometimes there is some confusion between the crime of human trafficking and other crimes, so it is necessary to analyse it from different perspectives in order to guarantee the protection of the victims. In this study a review has been made from different perspectives: approach to the centralization of the victim, approach to criminalization of crime or fight against crime, gender approach and approach based on human rights. The study has been focused on the last perspective because of the serious violation of human rights that affects in all aspects the victims’ legal sphere.
Keywords: human trafficking; human rights; crime; slavery; exploitation